Congenital connective tissue dysplasia and minor heart defects in children as a risk factor of psychic disorders - V.L. Kotlyarov; M.A. Kalinina; G.V. Kozlovskaya; G.N. Shimonova (LCC «Medicine-Inform», 2022)
V.L. Kotlyarov, M.A. Kalinina, G.V. Kozlovskaya, G.N. Shimonova Mental Health Research Center, Moscow, Russian Federation The article presents a short literature review highlighting a potential genesis of the disease and genetic background of congenital connective tissue dysplasia, as well as its association with certain congenital biochemical and mediator abnormalities. Over the past years, there has been a substantial growth of publications discussing a close relationship between connective tissue diseases and psychic deviations in children with autism and other endogenous disorders. Thus, the today's agenda focuses on a thorough investigation of abnormalities which may serve as somatic predictors of psychic disorders. This aspect is of particular importance for pediatricians who will be the first doctors dealing with such patients and may raise the issue of providing medical care rehabilitation care to them. Keywords: children, connective tissue dysplasia, mitral valve prolapse, diathesis, schizophrenia spectrum disorders. For citation: Kotlyarov V.L., Kalinina M.A., Kozlovskaya G.V., Shimonova G.N. Congenital connective tissue dysplasia and minor heart defects in children as a risk factor of psychic disorders. Russian Journal of Woman and Child Health. 2022;5(4):346-350 (in Russ.). DOI: 10.32364/2618-8430-2022-5-4-346-350.